The Effect Of Boiled Garlic Water On Reducing Blood Pressure In Hypertension Patients In The Area Of Kampung Curug RT 04 RW 04 Pakansari District, Bogor Regency - Hermawan, Denny Ardhy; Ramadhan, Gaung Eka; Dinaryanti, Ratna Sari (Sean Institute, 2024)
Hypertension is an abnormal increase in blood pressure. This occurs when arterioles contract. Arteriolar contraction makes blood flow difficult and increases pressure against the artery walls. Single garlic contains compounds such as allicin and hydrogen sulfide, which effectively break down blood clots in the arteries, thereby reducing blood pressure. This study aims to analyze the effect of boiled garlic water on lowering blood pressure in hypertensive patients in the RT 04 RW 04 Pakansari Village area. The research design uses a quasi-experimental method with a Non-randomized pretest and posttest without a control design. The sample size in this study is 24 respondents. The sampling technique used is purposive sampling. The instruments in this study are 4 grams of single garlic, 250 ml of warm water, a blender, a Sphygmomanometer, and a stethoscope. The statistical test used is paired T-test with the research results showing a significant effect on lowering blood pressure in hypertensive patients after being given boiled single garlic water with a p-value of 0.000. This indicates the influence of boiled garlic water on lowering blood pressure in hypertensive patients, and it is hoped that in the future, the results of this study can be used as one of the non-pharmacological therapies for grade I and grade II hypertensive patients.